2000
DOI: 10.1117/1.602557
|View full text |Cite
|
Sign up to set email alerts
|

Techniques and tools for obtaining symmetrical performance from tilted-component systems

Abstract: Tilted-component systems are known to be characterized by aberrations with unusual field dependences, such as decentered coma and binodal astigmatism. In this paper, the origin of binodal astigmatism in a multielement system from the contributions of individual surfaces is explained in an intuitive manner, as a logical extension of the ordinary aberrations known to all optical designers. The insight provided by this graphical model allows an understanding of why the astigmatism of any given system behaves the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Nodal aberration theory for optical imaging systems without symmetry (but with rotationally symmetric components) has emerged as an effective approach to describe the aberrations in misaligned or intentionally decentered/tilted optical systems [1][2][3]. We have recently demonstrated that the theory is well suited for the development of deterministic alignment strategies for astronomical telescopes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nodal aberration theory for optical imaging systems without symmetry (but with rotationally symmetric components) has emerged as an effective approach to describe the aberrations in misaligned or intentionally decentered/tilted optical systems [1][2][3]. We have recently demonstrated that the theory is well suited for the development of deterministic alignment strategies for astronomical telescopes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Figoski applied nodal aberration theory to find an alternate solution to a two mirror telescope problem 29 . Rogers illustrated an application of nodal aberration theory to guide the design of a head-worn display 30 .…”
Section: Applying Full-field Displays To Analyze the Dual-element Magmentioning
confidence: 99%
“…Each aberration type develops a characteristic field behavior in a system without symmetry. The astigmatic aberration field system without symmetry (misaligned) has, in general case, contain two zeros, or nodes, neither of which is necessarily located on the center of the image field [2,7] . The coma aberration, which depends linearly on field of view, the aberration field is completely unchanged except that it can move decentered from the center of the image field, if a system that corrected for third-order coma, the introduction of asymmetry will result in an optical system in which the third-order coma is constant in both magnitude and direction over the field of view.…”
Section: Introductionmentioning
confidence: 99%
“…However, The Nodal Aberration Theory (NAT) for optical system without symmetry (with rotationally symmetric components) has emerged as an effective approach to describe the aberrations in misaligned or intentionally decentered/tilted optical systems [1][2][3][4][5][6] . It has provided a complete mathematical representation of the aberrations of misaligned reflective optical systems in the context of the traditional third-order aberrations of Seidel [1] .…”
Section: Introductionmentioning
confidence: 99%